Social Portrait of the Participants in the Holocaust - Zagreckas, Rimantas (Genocidas ir rezistencija, 2012)
The events of the Holocaust in Lithuania have already been explored quite extensively and in some detail. It is clear that thousands of Lithuanians contributed to this tragedy. In addition to other very important questions, the question arises as to social characteristics of these people: these issues have not yet been explored. In this respect, the Lithuanian Special Archives (LSA) can provide a lot of information which is available in the criminal case fund of the USSR repressive institutions (LSA, f. K-1, ap. 58) held at the LSA. Using both historical and sociological methods, the files of 205 people sentenced for participation in the 1941 June Uprising in the counties of Biržai, Kėdainiai, Panevėžys, Rokiškis, and Utena (and who later contributed to the Holocaust) were examined in the documents of the said fund.It has been identified that the social status of those sentenced in 1941 essentially complies with the social structure typical of Lithuanian society and recorded in the Statistical Yearbook of Lithuania in 1938: the majority (up to 78% in Utena County and less elsewhere) of the convicts were farmers (the majority of these were small- and medium-sized farmers); craftsmen and blue-collar workers accounted for a far smaller number, and even fewer were white collar workers and members of the intelligentsia. The majority of people convicted in 1941 were men aged 20–40 years with little education (primary four-year education or less). A large proportion of them were married (they mostly got married at the age of 30–35 years). In the times of independent Lithuania, only a few of them (0–11% depending on the county) were involved in any political party or public organisation, 14–41% of them were members of the paramilitary Riflemen’s Union at some point.
Keywords: German occupation; Holocaust; collaborators